Characterization of the serological biomarkers associated with Sjögren’s syndrome in patients with recalcitrant dry eye disease - Matossian, Cynthia (Clin Ophthalmol, 2016)
PURPOSE: The purpose was to characterize the biomarkers associated with Sjögren’s syndrome (SS) identified in the serological samples of patients with recalcitrant dry eye disease; additionally, the modalities utilized in the treatment of dry eye disease were evaluated for subsets of patients with and without SS. PATIENTS AND METHODS: Data for this retrospective, single-center, pilot study were based on a chart review of 48 sequential patients with recalcitrant dry eye who were evaluated for SS via serological analysis. Data presented include the presence of the autoantibodies identified through the serological biomarker analysis and identification of the concurrent dry eye treatment modalities. RESULTS: Eleven out of 48 patients (23%) tested positive for biomarkers associated with SS. Autoantibodies for salivary protein-1, parotid secretory protein 1, and carbonic anhydrase VI, markers associated with the early development of SS, were detected in 91% (ten out of eleven) of the patients who tested positive for SS, whereas 27% (three out of eleven) of patients tested positive for the traditional SS markers, SS-A and/or SS-B. Common treatment modalities utilized in SS patients included omega-3 supplements (82%), topical cyclosporine (74%), and artificial tear solutions (64%), as compared to omega-3 supplements (80%), hot-mask therapy (77%), and artificial tear solutions (77%), in SS-negative patients. CONCLUSION: Evaluation for salivary protein-1, parotid secretory protein 1, and carbonic anhydrase VI biomarkers allows for identification of a subset of patients with biomarkers associated with SS that may not be identified through the traditional assessments (SS-A/SS-B). Earlier recognition of SS biomarkers allows for a confirmatory diagnosis and appropriate management of this systemic, progressive condition.